Relation between carbonation resistance, mix design and exposure of mortar and concrete. (September 2015) - Leemann, Andreas; Nygaard, Peter; Kaufmann, Josef; Loser, Roman
Abstract: When cement with mineral additions is employed, the carbonation resistance of mortar and concrete may be decreased. In this study, mortars containing mineral additions are exposed both to accelerated carbonation (1% and 4% CO2 ) and to natural carbonation. Additionally, concrete mixtures produced with different cements, water-to-cement ratios and paste volumes are exposed to natural carbonation. The comparison of the carbonation coefficients determined in the different exposure conditions indicates that mortar and concrete containing slag and microsilica underperform in the accelerated carbonation test compared to field conditions. The carbonation resistance in mortar and concrete is mainly governed by the CO2 buffer capacity per volume of cement paste. It can be expressed by the ratio between water added during production and the amount of reactive CaO present in the binder (w/CaOreactive ) resulting in a novel parameter to assess carbonation resistance of mortar and concrete containing mineral additions.